Expressive Speech Act of British and American Culinary Review: A Cross-Cultural Pragmatics Study - Kharismi, Annisa; Subiyanto, Agus (Bina Nusantara University, 2024)
The research was conducted to uncover how American and British high school students utilize expressive speechacts for each other’s culinary representation. It examined the linguistic and cultural manifestations in which reviewers communicated their personal opinions and attitudes toward food. The research applied a descriptivequalitative approach using Searle’s theory of the illocutionary point of speech act, which comprised the pragmatical characteristics focusing on the spoken form expression from both cultures. The data were collected from two video blogs from a YouTube channel called ‘Jolly’, with the title “British high-school students try American biscuits and gravy for the first time” and “Americans eat British comfort food for the first time” by using listening and note-taking techniques on the expressive speech act that occurred from the transcript of the video blog. The results show that both American and British high school students have expressive speech acts of surprise, preference, and disbelief. Yet, the unique traits of both cultures can be noticed in the way Americans express disgust while the British express humor.